Activation and blockade of dorsal hippocampal Serotonin6 receptors regulate anxiety-like behaviors in a unilateral 6-hydroxydopamine rat model of Parkinson's disease. (2nd September 2019) - Liu, Kun Cheng; Guo, Yuan; Zhang, Jin; Chen, Li; Liu, Yi Wei; Lv, Shu Xuan; Xie, Wen; Wang, Hui Sheng; Zhang, Yu Ming; Zhang, Li
ABSTRACT: Objectives : This study aimed to investigate the effect of serotonin6 (5-HT6 ) receptors in the dorsal hippocampus (dHip) on the regulation of Parkinson's disease (PD)-associated anxiety. Methods : We examined whether intra-dHip injection of both 5-HT6 receptor agonist and antagonist was involved in the regulation of anxiety-like behaviors in sham-operated rats and rats with unilateral 6-hydroxydopamine (6-OHDA) lesions of the medial forebrain bundle by the open-field and elevated plus maze (EPM) tests. Four weeks after injection of 6-OHDA, the concentrations of dopamine (DA), noradrenaline (NA) and 5-hydroxytryptamine (5-HT) in relative related brain regions were measured by reverse-phase high-performance liquid chromatography. Results : In sham-operated rats, intra-dHip injection of both 5-HT6 receptor agonist WAY208466 (3 and 6 µg/rat) and antagonist SB258585 (4 µg/rat) increased the percentage of time spent in the center area in the open-field test and percentages of open arm entries and open arm time in EPM test, indicating that induced anxiolytic effects. In the lesioned rats, WAY208466 (1.5, 3 and 6 µg/rat) produced anxiolytic responses, whereas SB258585 (2 and 4 µg/rat) produced anxiogenic effects. Neurochemical results showed that intra-dHip injection of WAY208466 (6 µg/rat) decreased NA level in the amygdala, and SB258585 (4 µg/rat) increased DA levels in the dHip and vHip in sham-operated rats, whereas WAY208466 increased DA levels in the dHip, vHip, and amygdala in the lesioned rats. Discussion : dHip 5-HT6 receptors are involved in the regulation of anxiety-like behaviors, which may be mediated through different neurochemical mechanisms, and the dHip is an important site involved in these effects. Abbreviation : PD: Parkinson's disease;6-OHDA: 6-hydroxydopamine; dHip: dorsal hippocampus; vHip: ventral hippocampus; 5-HT: serotonin; MFB: medial forebrain bundle; DA: dopamine; NA: noradrenaline; EPM: elevated plus-maze; GABA: gamma-aminobutyric acid; BLA: basolateral amygdala